In sacco, in vitro and in vivo digestibility and supplementary value of some tropical forage legume hays to sheep feeding on a basal diet of maize stover - Tolera, Adugna; Said, A.N. (Wiley, 1997)
The potential of Desmodium intortum, Macrotyloma axillare and Stylosanthes guianensis hays for improving the digestibility of a standard diet of maize stover was assessed using in sacco, in vitro and in vivo methods. In sacco degradability results showed that S. guianensis hay had the highest potential and effective DM degradability. S. guianensis hay also had higher (P<less than>0.05) in vitro DM digestibility than maize stover, D. intortum and M. axillare. In vitro DM digestibility was negatively correlated (r = <minus>0.97) with ADF content of the feeds. The in vivo data showed no significant differences among different species of legume hay supplements and levels of supplementation in DM and OM digestibility. The NDF, ADF and CP digestibility were higher (P<less than>0.05) in S. guianensis hay supplemented groups than groups supplemented with the other forage legume hays. This was associated with lower levels of ADF and lignin and higher CP content in S. guianensis hay. It is concluded that S. guianensis was better than the other 2 forage legumes in improving nutrient (CP, NDF, ADF and estimated in vitro DM) digestibility of maize stover-based diets. This may be due to low fibre content, increased nitrogen availability and improved rumen microbial activity.